Island migration and foraging behaviour by anatomically modern humans during the late Pleistocene to Holocene in Wallacea: New evidence from Central Sulawesi, Indonesia. - Ono, Rintaro (Archīum Ateneo, 2020)
Maritime migration and island adaptation by anatomically modern humans (AMH) are among the most significant issues in Southeast Asian anthropology and archaeology, and directly related to their behavioural and technological advancements. A major research hotspot is Wallacean islands located between the past Sunda and Sahul continents during the late Pleistocene. The gaps between the Wallacean islands and both landmasses are very likely the major factor for the relative scarcity of animal species originating from Asia and Oceania and the high diversity of endemic species in Wallacea. They are also considered as a barrier for hominin migration into Wallacean islands and Sahul continent. We report new archaeological research on the eastern coast of Sulawesi, which could have been the most potential location for the early AMH migration by sea crossings from the Maluku Islands along the northern routes towards Sahul. Based on the new findings, we discuss the evidence and timeline for migrations of early modern humans into the Wallacean islands. This includes an overview of the excavated stone and bone artefacts and faunal remains in the region in the context of changes in human foraging behaviour as well as the technological and cognitive aspects of human adaptation as a response to rapidly changing ecological conditions during the late Pleistocene to Holocene periods.